Multi-seconic words and their meanings in the Karachay-Balkar language - Fatima Kh. Akhmatova (Кавказология)
The article focuses on the subject of polysemy in the Karachay-Balkar language. Through polysemy, new concepts appear in a language without changing or with a slight change in the sound expression of these concepts. The development of polysemy is based on the figurative meaning or one meaning of an existing word to a new concept through the associative connection of ideas similar to them. Therefore, an unconditional condition for the development of polysemy is the stability of the phonetic word, which in turn is determined by the concept it expresses. Polysemy should be recognized as an important method of expanding vocabulary, particularly the root word. The main obstacle to detect and define new meanings of words stems from the fact that a new meaning might emerge and disappear in a relatively short period, while other meanings emerge and firmly enter the language lexicon, preserving word frequency. However, all these changes are not always recorded in dictionary entries and this phenomenon in the modern language is one of the key problems and requires identifying ways to solve it.